Being peace - Hanh, Thich Nhat (b, 2005)
An ideal starting point for those interested in Buddhism, Being Peace contains Thich Nhat Hanh's teachings on peace and meditation. Using real examples from his own life, as well as poems and fables, Nhat Hanh explains his key practices for living "right in the moment we are alive." These lessons are taught with fine writing and sparkling phrases that draw the reader in.
Keywords: v; Buddhism. -- Doctrines; Religion and Psychology